Hukum Acara Perdata dalam Penyelesaian Sengketa Perdata: Tinjauan Teori Hukum Responsif Nonet dan Selznick - I Putu Windu Semara Putra; I Gede Agus Kurniawan (Faculty of Law, Universitas Pekalongan, 2025)
Civil procedural law is the primary instrument for resolving civil disputes in court. However, in practice, criticism often arises that existing procedures tend to be rigid, formalistic, and do not always meet the needs of justice seekers. The responsive legal theory developed by Nonet and Selznick offers an analytical framework for assessing the extent to which the legal system is able to adapt to the aspirations and interests of society. This study aims to examine how civil procedural law in Indonesia functions in resolving civil disputes and to assess the extent to which its application can be categorized as responsive law, according to Nonet and Selznick's theory. This study uses a normative-juridical approach with a literature review. Data were obtained from relevant laws and regulations, legal literature, and court decisions, then analyzed qualitatively through the perspective of responsive legal theory. The analysis shows that although civil procedural law has provided a formal mechanism for resolving disputes, its implementation is often procedural and slow. This creates a gap between legal norms and the reality of justice seekers. Within the theoretical framework of Nonet and Selznick, Indonesian civil procedural law tends to be at the stage of